IMPLEMENTASI MANAJEMEN BIMBINGAN KONSELING DALAM PEMBENTUKAN KARAKTER SISWA MELALUI SELF ACCEPTANCE DI SDIT LAA TAHZAN CITRA - Dina Ayu Setiani; Uswah (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to describe the implementation of guidance and counseling (BK) management in shaping student character through a self-acceptance approach at SDIT Laa Tahzan Citra, Cikupa District, Tangerang Regency. The problem of low self-acceptance in elementary school students is a concern because it can affect their character development. Therefore, planned, integrated, and appropriate guidance and counseling services are needed. This study applies a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. Research informants include the principal, BK teachers, class teachers, and representatives of student affairs. The results show that BK management at SDIT Laa Tahzan Citra is implemented through several stages, namely program planning based on student needs, implementation of individual and group counseling services, activity control, and informal evaluation. In its implementation, grounding and emotional acceptance techniques are used to help students understand, accept, and manage emotions positively. Character building efforts are also strengthened through school habituation programs, such as dhuha prayer and student activities, which play a role in instilling religious values, discipline, and self-confidence. Collaboration between guidance counselors, homeroom teachers, and the principal is a crucial factor in the success of guidance and counseling services. The implementation of self-acceptance has a positive impact on increasing students' self-confidence, emotional control, and the quality of their social relationships. However, this study also found that program documentation and assessment instruments need to be improved to ensure more systematic and measurable guidance and counseling services.